2020
DOI: 10.3390/rs12152447
|View full text |Cite
|
Sign up to set email alerts
|

UAV Photogrammetry Accuracy Assessment for Corridor Mapping Based on the Number and Distribution of Ground Control Points

Abstract: Unmanned aerial vehicle (UAV) photogrammetry has recently emerged as a popular solution to obtain certain products necessary in linear projects, such as orthoimages or digital surface models. This is mainly due to its ability to provide these topographic products in a fast and economical way. In order to guarantee a certain degree of accuracy, it is important to know how many ground control points (GCPs) are necessary and how to distribute them across the study site. The purpose of this work consists of determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
63
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 36 publications
0
63
0
6
Order By: Relevance
“…Others have used sUAV-based methods to monitor changes in coastline due to wave run up [18] and evaluate water resource infrastructures such as spillways [15]. Similar to this study, other studies have also evaluated various parameters on procedures and their effect on accuracy including altitude, ground control, camera angle, and others [5,[32][33][34][35][36]. This is not an exhaustive review, and many more examples of using sUAV data and SfM algorithms to generate terrain data and to explore the impact of various parameters and processes exist.…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…Others have used sUAV-based methods to monitor changes in coastline due to wave run up [18] and evaluate water resource infrastructures such as spillways [15]. Similar to this study, other studies have also evaluated various parameters on procedures and their effect on accuracy including altitude, ground control, camera angle, and others [5,[32][33][34][35][36]. This is not an exhaustive review, and many more examples of using sUAV data and SfM algorithms to generate terrain data and to explore the impact of various parameters and processes exist.…”
mentioning
confidence: 81%
“…Research has shown that without RTK GPS and high-precision IMUs, accurately projecting point clouds to a reference datum requires GCPs [5]. We experimented with not including GCPs in a small, local area at Newcastle Dam and in mis-tagging a GCP in one image.…”
Section: Gcp Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Satellites, airplanes, and unmanned aerial vehicles (UAVs) have been the main carriers in the acquisition of remote sensing images. In particular, the UAV has the advantages of strong maneuverability, convenient operation, being hardly influenced by cloud, strong data acquisition abilities [1][2][3], etc., which make it widely applied in various fields [4][5][6][7][8][9][10][11][12]. How to efficiently locate the UAV images without geo-tags and navigate the UAV when the positioning system (e.g., GPS) is not available still face great challenges that are expected to be solved.…”
Section: Introductionmentioning
confidence: 99%